The Effect of Digital Marketing and Personal Branding on Consumer Purchase Decisions of Culinary MSMEs in Jakarta Moderated Consumer Perception - Kustiadi Basuki; Jeremia Jimmy (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Utilization of technology Digital marketing in the world of marketing is becoming a very common thing to do. Especially for businesses with small and medium scale businesses (UMKM) engaged in the culinary field. Therefore, this study aims to examine and analyze the effect of digital marketing and personal branding on consumer purchasing decisions in Jakarta moderated by consumer perception. The population in this study are consumers of culinary SMEs in Jakarta. The data collection technique used random sampling by distributing questionnaires via google form. From the results of the tests carried out, it was found that digital marketing was not able to influence consumer decisions, personal branding able to influence consumer decisions, consumer perception able to influence consumer decisions, Moderation of consumer perception was not able to strengthen the influence of digital marketing on consumer decisions and moderation of consumer perception weakened personal branding on consumer decisions.